The pluripotency transcription factor OCT4 represses heme oxygenase-1 gene expression - Petrone Parcero, María Victoria (2021)
In embryonic stem (ES) cells, oxidative stress control is crucial for genomic stability, self-renewal, and cell differentiation. Heme oxygenase-1 (HO-1) is a key player of the antioxidant system and is also involved in stem cell differentiation and pluripotency acquisition. We found that the HO-1 gene is expressed in ES cells and induced after promoting differentiation. Moreover, downregulation of the pluripotency transcription factor (TF) OCT4 increased HO-1 mRNA levels in ES cells, and analysis of ChIP-seq public data revealed that this TF binds to the HO-1 gene locus in pluripotent cells. Finally, ectopic expression of OCT4 in heterologous systems repressed a reporter carrying the HO-1 gene promoter and the endogenous gene. Hence, this work highlights the connection between pluripotency and redox homeostasis.